2016
DOI: 10.1038/icb.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A6 regulates interleukin‐2‐mediated T‐cell proliferation

Abstract: Annexin A6 (AnxA6) has been implicated in cell signalling by contributing to the organisation of the plasma membrane. Here we examined whether AnxA6 regulates signalling and proliferation in T cells. We used a contact hypersensitivity model to immune challenge wild-type (WT) and AnxA6(-/-) mice and found that the in vivo proliferation of CD4(+) T cells, but not CD8(+) T cells, was impaired in AnxA6(-/-) relative to WT mice. However, T-cell migration and signalling through the T-cell receptor ex vivo was simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 76 publications
(172 reference statements)
1
25
0
Order By: Relevance
“…In good agreement with this finding, we observed increased mRNA expression of IL-2 as central activator of T cell proliferation [19] in the spleen of aSyn −/− mice on day 10 after EAE induction, whereas mRNA expression of IL-4 as key cytokine during Th2 cell-mediated immune response was unaltered. These data suggest that α-synuclein deficiency leads to increased IL-2 production, thereby expanding the population of Th1 cells.…”
Section: Discussionsupporting
confidence: 85%
“…In good agreement with this finding, we observed increased mRNA expression of IL-2 as central activator of T cell proliferation [19] in the spleen of aSyn −/− mice on day 10 after EAE induction, whereas mRNA expression of IL-4 as key cytokine during Th2 cell-mediated immune response was unaltered. These data suggest that α-synuclein deficiency leads to increased IL-2 production, thereby expanding the population of Th1 cells.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with earlier studies (Hawkins et al, 1999) (Cornely et al, 2016). To elicit an immune response, mice were then subjected to a delayed-type contact hypersensitivity reaction.…”
Section: Anxa6 Ko Micementioning
confidence: 70%
“…30,111 Likewise, although our recent studies suggested that the absence of AnxA6 in T-lymphocytes destabilized the organization of the plasma membrane, T-cell migration and signaling was not affected in AnxA6-deficient T-lymphocytes. 63 Also, in chick midbrain neural crest cell development, AnxA6 depletion attenuated, while AnxA6 overexpression enhanced neural crest cell emigration, respectively. 112 However, opposing cellular activities as observed for AnxA6 are not uncommon, as loss of another scaffold protein, caveolin-1 (Cav-1), predicts poor clinical outcome in some cancers, while its overexpression is linked to aggressive and metastatic behavior in others.…”
Section: Anxa6 and Recruitment Of Signaling Proteinsmentioning
confidence: 95%
“…54 Likewise, analysis of laurdan-stained T cells isolated from WT and AnxA6 ¡/¡ mice supported AnxA6 to alter the membrane environment in the plasma membrane. 63 From these observations we predicted consequences in the distribution of cell surface proteins. Indeed, PALM superresolution microscopy identified association of AnxA6 up/downregulation with differential and cell-specific differences in the cholesterol-sensitive microdomain distribution of membrane-anchored, fluorescent raft and nonraft marker proteins.…”
Section: Annexin A6 and Remodeling Of Plasma Membrane Domainsmentioning
confidence: 99%